Effects of noise to the industrial workers at PCB assembly industry - Sarsikumar, Easwaran; Nafrizuan, Mat Yahya (Penerbit UMP, 2024)
In today's environment, working conditions in factories, such as lighting, temperature, and noise, need to be studied to show the specific sections of a factory. Any sound that is annoying or exceeds 90 dBA may be considered noise. There are noise exposure issues at the production site of a PCB assembly industry in Johor Bahru. However, no research measures noise exposure in all selected departments at this company. Noise can cause negative emotions, delay sleep, disturb rest, and make it challenging to hear desirable sounds. However, studies have not been conducted on noise effects on industrial workers in the PCB Assembly Industry. This study investigated noise's effect on industrial workers. The SMT, Backend, and Warehouse departments were selected for the research study. Forty questions on different aspects of noise effects were prepared and served to 150 workers in three departments. Responses from workers were collected, which served as data for further analysis. A well-known statistical test called the Chi-Square test was used to determine the significance of noise effects. At the level of significance α = 0.10 and α = 0.05, it was found that the Physiological Effect, Hearing Loss Effect, Auditory Effect, Psychological Effect and sleep disturbance were significant. A discussion is highlighted, and the paper concludes with the study's essential findings.